Lignans from leaves of Amesiodendron chinense and their cytotoxic activity - Ban, Ho Van; Van, Trinh Thi Thanh; Chien, Vu Van; Hue, Nguyen Thi; Hang, Pham Thi; Tuan, Nguyen Le; Nhiem, Nguyen Xuan; Cuong, Pham Van; Vuong, Nguyen Quoc (Vietnam Journal of Science and Technology, 2020)
ABSTRACT From leaves of Amesiodendron chinense (Mer.) Hu four lignans (+)-aptosimon (1), (+)-isolariciresinol (2), (-)-cleomiscosin A (3), and (-)-cleomiscosin C (3) were isolated. Their structures were determined by spectroscopic analysis including MS, 1D and 2D NMR as well as by comparison with reported data in literature. All compounds were evaluated for cytotoxic activities against five human cancer cell lines, KB, SK-LU-1, MCF-7, HepG-2, and SW-480. They showed weak cytotoxic activity on five tested human cancer cell lines with IC50 values ranging from 32.61 to 95.18 µg/ml.